Integrative taxonomy of new firefly taxa from the Atlantic Rainforest. Issue 4 (3rd July 2016) - Silveira, Luiz; Khattar, Gabriel; Souto, Paula; Mermudes, José Ricardo M.; Takiya, Daniela M.; Monteiro, Ricardo F.
Abstract : Tropical mountains are hotspots of biodiversity, hosting many endemic species. Here, we propose Luciuranus gen. nov. and four new firefly species dwelling in montane habitats of the Brazilian Atlantic Rainforest. Luciuranus gen. nov. is unique in the shape of the last abdominal segments of both males and females, varying in a clear species-specific fashion. Luciuranus josephi sp. nov. and L. jameshooki sp. nov. are restricted to Serra dos Órgãos mountain range, while L. dextrus sp. nov. and L. sinistrus sp. nov. are restricted to Serra da Mantiqueira formation. DNA barcoding with COI gene confirmed species identities and male–female associations. We propose that terminalia structures work together as a lock-and-key mechanism, avoiding hybridization in overlapping zones along heterogeneous habitats, such as montane forests, where temperature, moisture, and vegetation cover can change significantly even in small spatial and temporal scales. Such morphological displacement is discussed in terms of sexual selection on both male and female features. We also provide detailed morphological descriptions, illustrations, and a key to species based on males and females. http://zoobank.org/urn:lsid:zoobank.org:pub:05598351-4655-49E5-9011-B90DFC7D9435